2024
DOI: 10.1001/jamapsychiatry.2024.0804
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Mental Disorders and Suicide Attributable to Childhood Maltreatment

Lucinda Grummitt,
Jessie R. Baldwin,
Johanna Lafoa’i
et al.

Abstract: ImportanceThe proportion of mental disorders and burden causally attributable to childhood maltreatment is unknown.ObjectiveTo determine the contribution of child maltreatment to mental health conditions in Australia, accounting for genetic and environmental confounding.Design, Setting, and ParticipantsThis meta-analysis involved an epidemiological assessment accounting for genetic and environmental confounding between maltreatment and mental health and 3 cross-sectional national surveys: the Australian Child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis found that childhood maltreatment could account for 21% to 41% of common mental health problems (e.g. depression, suicide attempts) in Australia (Grummitt et al, 2024 ), highlighting the potentially significant effects of trauma and adversities. Previous studies have further indicated that interpersonal trauma, particularly betrayal trauma or violence committed by someone close to the victim (such as a family member), can have more severe consequences than non-interpersonal trauma (such as natural disasters or car accidents) (Chiu et al, 2017 ; López-Martínez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis found that childhood maltreatment could account for 21% to 41% of common mental health problems (e.g. depression, suicide attempts) in Australia (Grummitt et al, 2024 ), highlighting the potentially significant effects of trauma and adversities. Previous studies have further indicated that interpersonal trauma, particularly betrayal trauma or violence committed by someone close to the victim (such as a family member), can have more severe consequences than non-interpersonal trauma (such as natural disasters or car accidents) (Chiu et al, 2017 ; López-Martínez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%